Assessing Readiness for Change of Juvenile Probation Policies and Practices: A Factor Analysis of the Probation Officer Attitudes, Beliefs, and Behavior (POABB) Scale (Journal of Applied Juvenile Justice Services, 2023)
As juvenile probation undergoes nationwide reform to better align with research on adolescent development, it is critical to understand probation officers’ knowledge, attitudes, and beliefs about corresponding changes to supervisory practices within juvenile probation departments. The Probation Officer Attitudes, Beliefs, and Behaviors (POABB) Scale was designed for use with juvenile probation officers (JPOs) undergoing training in a specific evidence-based supervision strategy (i.e., Graduated Response) to assess staff’s knowledge and beliefs about Graduated Response’s practices and intended supervisory behaviors. To provide foundational empirical support for the novel scale, the current study examined the factor structure of this self-report measure using POABB data from 351 juvenile probation staff across three mid-Atlantic states. An exploratory factor analysis revealed that a five-factor structure within the POABB provided the best fit and, overall, the POABB had good internal reliability (ɑ = 0.84). Importantly, the five-factor structure suggests a key difference between knowledge of Graduated Response components and attitudes toward using those components in everyday practice. Results suggest that use of the POABB can provide probation departments with information about specific attitudes and overall willingness to implement specific supervision practices as well as offer targeted areas for additional training to support developmentally appropriate probation transformations.